Reviving and preserving the values of Malay traditional costume (MTC) in Malaysia / Zainudin Md Nor - Md Nor, Zainudin (Institute of Graduate Studies, UiTM, 2018)
The purpose of this study is to identify the pattern development and values of the Malay Traditional Costumes (MTCs) which have always been said by researchers and local culturalists as being eroded by the effects of modernization. The main research focuses on the outfits of the Malay females and males. It is also related to its headgears and accessories. This research identifies and justifies the factors that contribute to the best environment to maintain the methods, values and cultures of wearing traditional Malay costumes. Both quantitative and qualitative methods were used in conducting the research. The study used questionnaire survey, interviews and observation. Direct and indirect questions were used as an interview method. It also involved participants' observation and inspection of the costume artefacts. 78 pieces of old Malay costumes were seen and recorded for analysis. The researcher also interviewed 60 respondents who were experienced and experts in their field of making and styling traditional Malay costumes; such as old tailors and old dressmakers, fashion designers, industrialists, choreographers, culturalists, researchers and lecturers. The questionnaire was also forwarded to 26 teachers and 380 secondary school students in Perak, Kedah, Penang and Perlis. A small group of the respondents was chosen as a case study as they were able to produce, maintain and restore the traditional Malay costumes. The findings show that there is a significant relationship among five component values for future development and sustainability in the MTCs which are cultural and heritage values, educational values, art and aesthetic values, design and functional values and lastly socio economic values. This research has also found that the documentation on the development of pattern, style and cutting of the MTCs is relevant and can help to perpetuate it for future generations. The existence of ethics, philosophy, artistic (symbol) and aesthetic (meaning) values of the MTCs contributes new knowledge to the public. MTCs also have a relationship with other forms of Malay art such as architecture, literature, social manner and Islamic values. In conclusion the policy makers or government agencies, NGOs, practitioners, researchers, media and institutions of higher learning can play a major role in reviving and preserving the value of MTCs. This research recommends that integration among these groups is a vital factor that contributes to the creation of a model of good practice for future development of Malay traditional costumes in Malaysia.